Design and Construction of the Binjai City BPBD Website Using PHP and MySQL - Zuhri Ramadhan; Fachrid Wadly (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The Regional Disaster Management Agency (BPBD) of Binjai City plays a crucial role in distributing logistical aid to communities affected by disasters. The manual recording and distribution process currently in use often leads to challenges such as delayed information, recording errors, and difficulties in monitoring stock in real time. This study aims to design and develop a web-based logistics information system using PHP programming language and MySQL database. The development method applied is the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance stages. The system includes features for managing administrator data, item categories, item records, and aid distribution, all integrated in real time. Testing results indicate that the system improves efficiency in stock recording and tracking, accelerates aid distribution, and enhances accuracy and accountability in BPBD Binjai's logistics management.